Co-Rumination of Fat Talk and Weight Control Practices: An Application of Confirmation Theory. Issue 4 (3rd April 2017) - Arroyo, Analisa; Segrin, Chris; Harwood, Jake; Bonito, Joseph A.
ABSTRACT: Grounded in confirmation theory, the current research sought to explore the relationship between co-rumination of fat talk and weight control practices (i.e., binging and purging, exercising, and healthy eating behaviors), with a particular interest in whether perceptions of friends' responses during these interactions exacerbate or mitigate this relationship. Female friendship dyads completed online questionnaires at three time points across 2 weeks. Multilevel modeling analyses revealed that (a) co-rumination was positively associated with binging and purging and exercising, (b) women who perceived their friends as accepting reported less binging and purging, more exercising, and more healthy eating behaviors, (c) acceptance and challenge interacted to predict binging and purging, (d) acceptance moderated the relationships between co-rumination and binging and purging, and (e) challenge moderated the relationship between co-rumination and healthy eating behaviors.